Ligand-based Design, Synthesis and Primary in vivo Screening of Pyrrole Derivatives as Potential Tricyclic Anti-inflammatory Agents - Bijev, Atanas; Yaneva, Diana; Bocheva, Adriana; Stoev, Georgi (Arzneimittelforschung, 2006)
Twelve new compounds were designed as 5-aryl-1H-pyrrole analogs of celecoxib (CAS 169590-42-5) and were synthesized by Paal-Knorr cyclization in three series according to 1 H-substitution: derivatives with salicylic acid, pyrazolone or isonicotinamide residues. The average physico-chemical and steric similarity between the prototype and the new analogs (completed with two previously synthesized related products) was assessed to be 82 % and therefore considered as a reliable prerequisite for spatial compatibility and effective binding to the cyclooxygenase (COX) enzymes.The anti-inflammatory effects were determined in acute inflammation model using the carrageenan-induced rat paw edema assay on male Wistar rats (180–200 g) at doses of 10, 20 and 40 mg/kg, i.p. Six of the new products showed higher percent of inhibition (up to 100 %) compared to the highly selective COX-2 inhibitor celecoxib and the nonselective indometacin (CAS 53–86–1) used as reference compounds. Ethyl 1-(1,5-di-methyl-3-oxo-2-phenyl-2,3-dihydro-1H-4-pyrazolyl)-2-methyl-5-phenyl-1H-3-pyrrolecarboxylate (2b), ethyl 5-(4-chlorophenyl)-2-methyl-1-[(4-pyridylcarbonyl) amino]-1H-3-pyrrolecarboxylate (3c) and 5-[3-acetyl-2-methyl-5-(4-methylphenyl)-1H-1-pyrrolyl]-2-hydroxybenzoic acid (4b) were pointed out as the most active representatives of each of the three tested sub-series.
Keywords: Anti-inflammatory drugs, non-steroidal; Carrageenan-induced inflammation; Pyrrole derivatives, anti-inflammatory action, synthesis